On-farm management of agricultural biodiversity in Nepal: Good practices - Revised edition 2012 - Sthapit, B.; Shrestha, P.; Bioversity International; Local Initiatives for Biodiversity, Research and Development; Nepal Agricultural Research Council (2012)
The book includes a set of community-based management practices of agricultural biodiversity such as participatory four cell analysis that allows analysis of the amount and distribution of local crop diversity and farmer’s rationale of such distribution; documenting traditional knowledge and diversity inventory using community biodiversity register, diversity block for verification and multiplication of seed, diversity kits to redistribute rare and unique varieties and improve access and availability through social seed network and community seed bank to provide an local institution to save, store and exchange of local germplasm and associated knowledge and a platform of social learning. Such platform is used to blend traditional and scientific knowledge i) to improve local crop diversity through participatory landrace enhancement or participatory crop improvement, and ii) to increase demand of local crop diversity by value addition and marketing interventions. The first edition was published by Bioversity International (2006) by IDRC support and because of huge demand of this publication, the revised edition was published by LI-BIRD with financial supported by Development Fund.